Role of diet and lifestyle modification in the management of nonalcoholic fatty liver disease and type 2 diabetes - Orsu Prabhakar; Mylipilli Bhuvaneswari (Tzu Chi Medical Journal)
Nonalcoholic fatty liver disease (NAFLD) is considered as the hepatic evidence of insulin resistance which is the hallmark of type 2 diabetes. NAFLD is considered as the risk factor for developing type 2 diabetes and has a high frequency of occurrence in those with existing type 2 diabetes. Compared with patients with only NAFLD or type 2 diabetes, these patients show a poor metabolic profile and increase mortality. Hence, effective treatment strategies are necessary. Here, we review the role of diet and lifestyle modification in the management of NAFLD and type 2 diabetes. Based on the available studies, it has been shown that the addition of any kind of physical activity or exercise is beneficial for patients with both NAFLD and type 2 diabetes. Proper dietary management leads to weight loss are also effective in improving metabolic parameters in patients with both NAFLD and type 2 diabetes. In conclusion, it is clear that increasing physical activity or exercise is effective in improving metabolic parameters in patients who are suffering with both NAFLD and type 2 diabetes.